Pola Enkulturasi Nilai-Nilai Islam dalam Keluarga Masyarakat Minangkabau Tradisional - Jonson Handrian Ginting; Afrida Afrida (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study investigates the patterns through which Islamic values are enculturated within traditional Minangkabau families, focusing on how a matrilineal social structure sustains the intergenerational transmission of religious and cultural values. Despite the prominence of Minangkabau society as the world's largest matrilineal community, the mechanisms through which Islamic values are preserved across generations remain insufficiently examined. Employing a qualitative design based on library research and archival analysis, the study draws upon classical manuscripts, historical records, scholarly literature, and biographies of prominent Minangkabau Muslim figures. The findings demonstrate that the enculturation of Islamic values is realized through an interconnected social system in which the extended family serves as the primary agent of value transmission, the surau functions as the principal institution for religious education and character formation, and the tradition of merantau facilitates the social maturation of men through experiential learning. This process is perpetuated through a cyclical return-to-village pattern, whereby migrants establish new families and reproduce the same religious and cultural values for subsequent generations. The study concludes that Islamic value enculturation in traditional Minangkabau society is fundamentally collective rather than individual, operating through an enduring network that integrates kinship, religious institutions, and social mobility into a sustainable model of cultural continuity.